Analyzing students' confusion in integration and differentiation techniques in calculus / Siti Asmah Mohamed, Nurhafizah Ahmad and Fadzilawani Astifar Alias - Mohamed, Siti Asmah; Ahmad, Nurhafizah; Alias, Fadzilawani Astifar (Unit Penerbitan JSKM, 2025)
This study investigates engineering students' confusion in mastering integration and differentiation techniques in calculus and its impact on their academic performance. A quantitative approach is employed, analyzing students' final examination responses to identify misconceptions and recurring errors. The study aims to determine the extent of confusion, examine its effect on students’ mathematical competency, and propose pedagogical strategies for improvement. The findings highlight key difficulties in selecting appropriate techniques, applying differentiation rules, and handling algebraic manipulations. Addressing these challenges is crucial in enhancing students' comprehension and problem-solving skills in calculus